Propriedades de concreto permeável contendo resíduo de caulim - Bezerra, Diego de Paiva (2023)
The development of urban centers had as one of its consequences the growth of impermeable soil areas and thus the emergence of problems such as flooding and waterlogging. In this context, the term "Water Sensitive Cities" appears, which are sustainable measures adopted so that the development of cities interferes the least in the natural water cycle, among these measures can be mentioned the permeable concrete (CoPe). In addition, the inclusion of alternative materials, such as industrial waste, in the composition of CoPe has been a relevant theme in research, in order to enhance the properties of pervious concrete and establish a recycling policy for this waste. Among the various industrial wastes, in the state of Paraíba, the coarse fraction of kaolin waste (RC), known as tantrum, deserves to be highlighted. The RC presents characteristics of porous aggregate, and good performance regarding adsorption, and may contribute to the permeability of CoPe. Given the above, the research aimed to investigate the influence of RC on the properties of permeable concretes. For this, a reference mixture was defined in the proportion 1:2:2:0.3 (cement: gravel 0: gravel 1: w/c). Subsequently, substitutions of conventional aggregate by RC were performed in the proportions of 10, 20, 30 and 40% in relation to the mass amount of gravel 0. These mixtures were evaluated in the fresh and hardened states. After comparing the results of the mixtures with RC and the reference, it was verified that the mixtures with 10 and 20% of substitution presented the highest increases in permeability coefficient. These mixtures reached the lowest mechanical strengths, while the opposite occurred in mixtures with 30 and 40% substitution. The RC30 mixture reached the highest values of uniaxial compressive strength (9.44 MPa) and flexural tensile strength (2.56 MPa), with a permeability coefficient of 1.03x105 mm/h in the dry state, representing an increase of 55% compared to the reference mixture and remaining within the values required by standard, classifying it for use in sidewalks for light traffic according to NBR 16416 (ABNT, 2015). Thus, the partial replacement of 9.5 mm fine aggregate by 30% RC contributed to the drainage functionality without compromising the mechanical performance of CoPe, indicating that this waste has the potential to be used in this type of concrete.